Comparative Analysis of the Financial Performance of the Food and Beverage Industry before and during the Pandemic Period - Budiman Rahmad; Dudi Rudianto (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This study seeks to analyze the decline in financial performance in the form of profitability, namely the ratio of return on assets (ROA), return on equity (ROE), gross profit margin (GPM), operating profit margin (OPM), and net profit margin (NPM) in the Covid-19 period against the period before Covid-19 in food and beverage industry companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. Methodology/approach – The population of this study is in the form of financial reports of food and beverage industry companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The sampling technique used purposive sampling method and obtained a total sample of 24 companies. This study uses Paired T test analysis (SPSS version 24 program) for its data analysis method. This study conclude that the return on assets (ROA) ratio, and return on equity (ROE) ratio experienced a significant decrease, while the gross profit margin (GPM) ratio, operating profit margin (OPM) ratio, and net profit margin (NPM) ratio did not experience a significant decrease in the Covid-19 period against the period before Covid-19.